Design and synthesis of semicarbazones and their bio-isosteric analogues as potent anticonvulsants: The role of hydrogen bonding - Pandeya S.N.; Agarwal A.K.; Singh A.; Stables J.P. (My University, 2025)
A series of p-nitrophenyl substituted semicarbazones (4a-c) and phenoxy/p-bromophenoxy acetyl hydrazones (8a-q) were synthesized and their anticonvulsant activity was screened against maximal electroshock seizure (MES), subcutaneous metrazole (ScMet) and subcutaneous strychnine (ScSty) tests. Compounds 4a-c with -NHCO- were found to be the most active in all these tests. These compounds were also active in the MES test after oral administration in rats. On the other hand, compounds 8a-q with -OCH2- were devoid of anticonvulsant activity. The studies revealed that the hydrogen bonding domain in semicarbazones, adjacent to the lipophilic aryl ring, is essential for the anticonvulsant activity.